Irinotecan in chemotherapy of advanced colorectal cancer - Leśniewski-Kmak, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2006)
Irinotecan (CPT-11) is a semisynthetic derivative of camptothecin, which effectiveness and toxicity have been extensively investigated in colorectal cancer (crc) and in this type of neoplasm it has wide application. Promising outcomes of early trials with CPT-11 and crc patients have been confirmed in randomized trials. In 5-fu-refractory crc patients, irinotecan showed advantage over best supportive care and infusions of 5-fu. Trials with CPT-11 in the first line treatment of crc also reported highest efficacy of this agent than 5-fu and leucovorin. Several trials have been conducted with irinotecan in schedules with targeted therapy agents and others, like oxaliplatin and oral precursor of 5-fu, capecytabine. An early trial with the oral form of irinotecan has also been reported.